Analysis of the First Three Waves of COVID-19 in West Africa Using an Epidemic Model With Different Modes of Transmission - Muhammad Said (Complexity, 2025)
COVID-19, although now at the endemic stage in numerous regions, is a serious public health challenge. While the virus spreads primarily through direct human-to-human contact, it can also be transmitted indirectly through contaminated environments. In this study, we propose a nonlinear epidemic model to analyze the first three waves of COVID-19 in Nigeria, Guinea, and Sierra Leone. Through the maximum likelihood method, we derive estimates for various parameters, including the direct transmission rate, indirect transmission rate, and initial infection rate. Our studies investigate changes in both direct and indirect transmission in the early waves of COVID-19 across West Africa, placing the virus’s behavior in perspective in several outbreaks. We also draw attention to the importance of consideration of structurally and practically identifiable combinations of parameters in producing realizations with biological significance. The results demonstrated significant variations in direct transmission rates, notably in Nigeria, whereas indirect transmission rates were generally steady across every country. It should be noted that direct transmission is higher compared with indirect transmission due to increased social interaction and mobility within the pandemic area. The low environmental survival of the virus is also a contributory factor to the limiting effect observed with indirect transmission. These pieces of evidence point to public health interventions that must focus on the prevention of direct transmission, such as the promotion of social distancing and mask use, with consideration for environmental factors. Our results emphasize the need for multiple control strategies to be considered for any future pandemic management in the region.